The Urgency of Applying the Concepts of Error in Persona and Aberratio Ictus in Substantive Criminal Law in Indonesia. - Putra Chinto Chamicho (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Â This study aims to examine the true nature of the concepts of error in persona and aberatio ictus from the perspective of legal dogma and their application in criminal law. The study employs legal research methods, utilizing primary and secondary legal materials and comparing them with existing regulations in several countries. The goal is to provide a fresh perspective on the concept and its practical application, as well as to examine its implications when applied to criminal law. The concepts of error in persona and aberatio ictus are not explicitly mentioned in the Criminal Code (KUHP), but its text clearly divides an act into two aspects of intention: intentional and unintentional.Â